Biogenic concrete protection driven by the formate oxidation by Methylocystis parvus OBBP - Ganendra, Giovanni; Wang, Jianyun; Ramos, Jose A.; Derluyn, Hannelore; Rahier, Hubert; Cnudde, Veerle; Ho, Adrian; Boon, Nico (Frontiers in Microbiology, 2015)
The effectiveness of Microbiologically Induced Carbonate Precipitation (MICP) from the formate oxidation by Methylocystis parvus OBBP as an alternative process for concrete protection was investigated. MICP was induced on Autoclaved Aerated Concrete (AAC), the model material, by immersing the material in 109 M. parvus cells mL-1 containing 5 g L-1 of calcium formate. A 2 days immersion of the material gave the maximum weight increase of the specimens (38 ± 19 mg) and this was likely due to the deposition of calcium carbonate, biomass, and unconverted calcium formate. The solid deposition mainly occurred in the micropores of the specimen, close to the outer surface. A significantly lower water absorption was observed in the bacterially treated specimens compared to the non-treated ones (up to 2.92 ± 0.91 kg m-2) and this could be attributed to the solid deposition. However, the sonication test demonstrated that the bacterial treatment did not give a consolidating effect to the material. Overall, compared to the currently employed urea hydrolysis process, the formate-based MICP by M. parvus offers a more environmentally friendly approach for the biotechnological application to protect concrete.